If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(w + -1) = 6w + 1 + -2(-6w + -1) Reorder the terms: 4(-1 + w) = 6w + 1 + -2(-6w + -1) (-1 * 4 + w * 4) = 6w + 1 + -2(-6w + -1) (-4 + 4w) = 6w + 1 + -2(-6w + -1) Reorder the terms: -4 + 4w = 6w + 1 + -2(-1 + -6w) -4 + 4w = 6w + 1 + (-1 * -2 + -6w * -2) -4 + 4w = 6w + 1 + (2 + 12w) Reorder the terms: -4 + 4w = 1 + 2 + 6w + 12w Combine like terms: 1 + 2 = 3 -4 + 4w = 3 + 6w + 12w Combine like terms: 6w + 12w = 18w -4 + 4w = 3 + 18w Solving -4 + 4w = 3 + 18w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-18w' to each side of the equation. -4 + 4w + -18w = 3 + 18w + -18w Combine like terms: 4w + -18w = -14w -4 + -14w = 3 + 18w + -18w Combine like terms: 18w + -18w = 0 -4 + -14w = 3 + 0 -4 + -14w = 3 Add '4' to each side of the equation. -4 + 4 + -14w = 3 + 4 Combine like terms: -4 + 4 = 0 0 + -14w = 3 + 4 -14w = 3 + 4 Combine like terms: 3 + 4 = 7 -14w = 7 Divide each side by '-14'. w = -0.5 Simplifying w = -0.5
| 8x+8=x+1 | | 2x(x-5)-(x-3)(x+2)=28-3(3x-1)(3x+2) | | t/27=-4 | | 2.5/y=5/12 | | 0.557=1-2.557*x | | 7/11=y/99 | | 4/9=24/z | | x^2-11x-51=0 | | x(x+1)=650 | | Y/12=2/3 | | 8y^7-7y^8=0.75 | | Y=8.5x-4 | | 4(3x-2)=2(5x-4) | | Tan^2x-secx=1 | | -3x-4(x+6)=-119 | | (3x-12)/(9-x) | | 16-6(x+12)=-2 | | 16-6(x-12)=-2 | | 8/4-6x3-4 | | 0.50/X=5/161.25 | | (o.50/X)=5/161.25 | | IK=3x+19 | | IK=3x | | HJ=22+2x | | 4(3-x)+x=22+2 | | 4a^2+8a=2 | | 5/18-4x/3=11/6 | | n-40-26=-3 | | -61=61*ln(x/120) | | x-2/5=11/15 | | 3(-14)/[5(-3)-7(-2)]= | | 2x-15+x=9 |